SOCIO-ENVIRONMENTAL DEGRADATION OF THE BACANGA RIVER: A CRITICAL LITERATURE REVIEW ON CHALLENGES AND PERSPECTIVES FOR NAVIGABILITY AND WATER MANAGEMENT (REMUNOM, 2026)
The navigability of urban water bodies is directly related to their environmental condition, the anthropogenic use of their banks, and the presence of adequate infrastructure for waterway circulation. In the city of São Luís, Maranhão, the Bacanga River stands out as one of the main waterways with historical, ecological, and functional potential for navigation, especially for small boats and traditional riverside activities. However, in the current context, the river is experiencing profound degradation and silting. Therefore, this study aimed to conduct a literature review to critically analyze and systematize the main environmental problems associated with the Bacanga River. It was found that restoring the navigability of the Bacanga River requires a perspective aligned with existing needs, encompassing the development of basic sanitation, efficient and sustainable environmental management, and the promotion of the socioeconomic development of riverside communities. This ensures the health of the population and the preservation of water resources, despite the tourism initiatives that seek to enhance their value.